Hsa-miR-100-3p Controls the Proliferation, DNA Synthesis, and Apoptosis of Human Sertoli Cells by Binding to SGK3 - Liu, Bang; Cui, Yinghong; Chen, Wei; Du, Li; Li, Chunyun; Wan, Cailin; He, Zuping (Frontiers in Cell and Developmental Biology, 2021)
Human Sertoli cell is required for completing the normal spermatogenesis, and significantly, it has important applications in reproduction and regenerative medicine because of its great plasticity. Nevertheless, the molecular mechanisms underlying the fate decisions of human Sertoli cells remain to be clarified. Here, we have demonstrated the expression, function and mechanism of homo sapiens-microRNA (hsa-miR)-100-3p in human Sertoli cells. We revealed that miR-100-3p was expressed at a higher level in human Sertoli cells by 10% FBS than 0.5% FBS. MiR-100-3p mimics enhanced the DNA synthesis and the proliferation of human Sertoli cells as indicated by EDU and CCK-8 assays. Flow cytometry showed that miR-100-3p mimics reduced the apoptosis of human Sertoli cells, and notably, we predicted and further identified SGK3 as a direct target of MiR-100-3p. SGK3 silencing increased the proliferation and decreased the apoptosis of human Sertoli cells, while SGK3 siRNA 3 assumed a similar role to miR-100-3p mimics in human Sertoli cells. Collectively, our study indicates that miR-100-3p regulates the fate decisions of human Sertoli cells by binding to SGK3. This study is of great significance since it provides the novel epigenetic regulator for the proliferation and apoptosis of human Sertoli cells and it may offer a new clue for gene therapy of male infertility.